Republic of Latvia : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that macroeconomic developments in Latvia were severely affected by the Russian economic crisis. Real GDP declined by 1.9 percent in the fourth quarter of 1998, and further contraction is estimated for the first quarter of 1999. As a consequence, the rate of unemployment rose to 10.1 percent in May, up from 7 percent a year earlier. Meanwhile, inflation has continued to fall amid continued tight monetary policy and weak domestic demand, reaching 1.9 percent in May.